LENGTH-WEIGHT RELATIONSHIP IN SAURIDA TUMBIL AND 5. UNDOSQUAMIS AND RELATIVE CONDITION IN S. TUMBIL - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
The length-weight relationship is useful for understanding the mathematical relationship between length and weight so that one may be converted into another. It is also useful to measure the ’Condition,’ i.e., the variation from expected weight for length of individual fish or groups of individuals as indications of fatness, general ’well being,’ gonad development, etc